The last resort during complex retrograde percutaneous coronary chronic total occlusion intervention: Extraplaque intracoronary lithotripsy to externally crush a heavy calcified occluded stent. Issue 2 (23rd December 2021) - Garbo, Roberto; Di Russo, Cristian; Sciahbasi, Alessandro; Fedele, Silvio
Abstract: Chronic total occlusions (CTO) due to in‐stent restenosis represent a challenging lesion subset for percutaneous coronary intervention in particular when associated with coronary calcification. Sometimes CTO lesions require antegrade or retrograde dissection‐re‐entry techniques with extraplaque dilation. Recently intravascular lithotripsy (IVL) emerged as a therapeutic option for the treatment of severely calcified coronary lesions but its role in extraplaque dilation is not described. In this report, we present a case of retrograde complex percutaneous coronary chronic total occlusion revascularization accomplished by the use of extraplaque IVL necessary to externally crush a heavy calcified previous implanted stent.